Hemodynamics Effects on Blood Movement through an Artery - Sharma, Sanjeev Kumar; Raghav, Jyoti Singh (International Journal of Computer Sciences and Engineering, 2018)
Mathematical simulation of blood movement in the arterial system certainly provides the nature and physiology of the creature body. Hemodynamic play the main role to build arterial single or multiple stenoses in the body, which indicate to the abnormalities of the cardio system. Blood functioning, especially in the diseased arteries can be identified by mathematical simulation. Applications of mathematical simulation can be used in surgical planning and configuration of medical devices. The arteries are such organs which can accept the change in varying hemodynamic conditions. In some cases, unusual hemodynamic impacts make an abnormal clinically response. The stenosis becomes the reason for turbulence and flows choking. In the arrival time, the investigation of arterial blood movement will give the prediction of hemodynamic movements in any patient. The advancement of clinical tools to identify the disease and modeling of devices will give better results.